Optical fiber Fabry-Perot interferometer with pH sensitive hydrogel film for hazardous gases sensing - Zheng, Yangzi (2018)
An optical fiber Fabry-Perot interferometer (FPI) coated with polyvinyl alcohol/poly-acrylic acid (PVA/PAA) hydrogel film for toxic gases measurement has been developed. Splicing a short section of hollow core fiber between two single mode fibers forms the FPI. Dip-coated pH-sensitive PVA/PAA hydrogel film on the fiber end performs as a receptor for binding of volatile acids or ammonia, which makes the sensing film swelling or shrinking and results in the dip wavelength shift of the FPI. By demodulating the evolution of reflection spectrum for various concentrations of volatile acids, a sensitivity of 20.8 nm/ppm is achieved with uniform linearity.